PENGHINAAN USTADZ MAAHER ATH-THUWAILIBI TERHADAP HABIB LUTHFI BIN YAHYA (KAJIAN SEMANTIK DAN PRAGMATIK) - Siti Julfiah; Muhammad Hasyim; Andi Agussalim (Journal of Innovation Research and Knowledge, 2023)
A case of humiliation occurred some time ago. The case dragged the name of Ustadz Maaher At-Thuwailibi (UMA). UMA is alleged to have insulted the figure of Nahdlatul Ulama (NU), Habib Luthfi bin Yahya (HLY), through his tweet on his Twitter account. The case began when UMA uploaded a photo of Habib Luthfi in a turban and called him 'beautiful wearing a hijab'. The photo was uploaded to reply to a tweet from the @gunduladul twitter account. UMA's tweet was reported to the Criminal Investigation Department. He was later named a suspect in alleged hate speech based on SARA. In this case, Ustadz Maaher is suspected of violating Article 45 paragraph (2) in conjunction with Article 28 paragraph (2) of Law number 19 of 2016. The objectives of this study: 1) examine UMA's utterances against HLY from a semantic perspective 2) understand the meaning of UMA's utterances if from a pragmatic point of view. The benefit of this research is to increase the knowledge base, especially in the field of forensic linguistics and become a useful reference for future research. This study used qualitative research methods. Based on the results of the research and discussion above, it can be concluded that: 1) Semantically, UMA utterances related to the words beautiful and hijab have meanings that are associated with women. This is further strengthened by the HLY photo which was uploaded along with the tweet. 2) Pragmatically, this statement wants to corner Nahdlatul Ulama, in this case Kyai and Banser. This is shown by the sentence of Banser's kyai, yes. 3) After analyzing both semantic and pragmatically, UMA's statement violates article 45 paragraph (2) in conjunction with article 28 paragraph (2) of law number 19 of 2016.